The Professional Identity of Three Innovative Teachers Engaging in Sustained Knowledge Building Using Technology - Vokatis, Barbara; Zhang, Jianwei (Frontline Learning Research, 2016)
Diffusing inquiry-based pedagogy in schools for deep and lasting change requires teacher transformation and capacity building. This study characterizes the professional identity of three elementary school teachers who have productively engaged in inquiry-based classroom practice using knowledge building pedagogy and Knowledge Forum, a collaborative online environment. Grounded theory analysis of teacher interviews, supplemented with field observations, highlights five distinctive features of the teachers’ identity: (a) Teachers as professional knowledge builders to explore new visions of teaching for continual improvement of knowledge building; (b) Teachers as co-learners to form symmetrical relationships with students so they can take on the highest level of responsibility; (c) Teachers as problem-solvers and barrier-breakers holding a proactive stance toward the contexts of practice; (d) Teachers as members of a professional community that encourages collaboration, innovation, and continual improvement; and (e) An empowering relationship with the Principal who supports teacher innovation and collaboration.